Jane Hiddleston. Writing After Postcolonialism: Francophone North African Literature in Transition. London: Bloomsbury Academic, 2017. - Beatrice Guenther (Studies in 20th & 21st Century Literature, 2018)
Review of Jane Hiddleston. Writing After Postcolonialism: Francophone North African Literature in Transition. London: Bloomsbury Academic, 2017. vii + 291 pp.
Keywords: postcolonialism; North Africa; Maghreb; Francophone literature